EFFECT OF CROP ESTABLISHMENT METHODS AND WEED MANAGEMENT PRACTICES ON YIELD AND YIELD ATTRIBUTES OF RICE (Oryza sativa L.) UNDER TEMPERATE CONDITIONS OF KASHMIR (Applied Biological Research, 2023)
Field experiments were conducted at the Faculty of Agriculture, SKUAST Kashmir, Wadura, Jammu and Kashmir during kharif seasons of 2017 and 2018 to assess the effect of crop establishment methods and weed  management practices on yield and yield attributes of rice (Oryza sativa L.)  under temperate conditions of Kashmir. The experiment comprised of three  seeding (DSR) and system of rice intensification (SRI)] and seven weed  management practices [butachlor @ 1500 g a.i. ha-1, penoxsulam (@ 22.5 g a.i. ha-1), pyrazosulfuran ethyl + pretilachlor (@ 15 and 600 g a.i. ha-1),  bensulfuron methyl + pretilachlor (@ 60 and 600 g a.i. ha-1), twice cono weeding/hand weeding, weed free and weedy check)] in sub-plots. The  treatments were replicated thrice in a split plot design. The results revealed  that SRI method of crop establishment gave significantly higher values for  yield attributes viz., number of panicles (399.15) and grains panicle-1(96.62)  that resulted in higher grain (8.04 t ha-1) and straw (9.88 t ha-1) yield as  compared to direct seeding and transplanted method. Among the weed  management practices, the application of penoxsulam (@ 22.5 g a.i. ha-1)  gave significantly higher grain (8.24 t ha-1) and straw (10.29 t ha-1) yield as  compared to other weed management practices, except weed-free and weedy check treatments. The average grain and straw yield increase with SRI was  24.11 and 23.62% over DSR and 10.47 and 12.23% over transplanted rice.  Highest B: C ratio of 1.60 was realized under SRI with the application of  penoxsulam @ 22.5 g a.i. ha-1.
Keywords: Economics; intensification; penoxsulam; system of rice transplanting; yield